2021
DOI: 10.3390/ijms22179119
|View full text |Cite
|
Sign up to set email alerts
|

Nature versus Number: Monocytes in Cardiovascular Disease

Abstract: Monocytes play a key role in cardiovascular disease (CVD) as their influx into the vessel wall is necessary for the development of an atherosclerotic plaque. Monocytes are, however, heterogeneous differentiating from classical monocytes through the intermediate subset to the nonclassical subset. While it is recognized that the percentage of intermediate and nonclassical monocytes are higher in individuals with CVD, accompanying changes in inflammatory markers suggest a functional impact on disease development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 100 publications
(141 reference statements)
0
27
0
2
Order By: Relevance
“…As an immune cell type, monocytes play a key role in inflammatory diseases (SahBandar et al, 2020 ). It has been demonstrated that monocytes are linked to the progression of CVD, and the level of monocytes can reflect the severity of CVD (Williams et al, 2021 ). In our study, the proportion of subjects who had hypertension, heart disease, and stroke in the SO group was higher than the proportion of similar subjects in the NSO group.…”
Section: Discussionmentioning
confidence: 99%
“…As an immune cell type, monocytes play a key role in inflammatory diseases (SahBandar et al, 2020 ). It has been demonstrated that monocytes are linked to the progression of CVD, and the level of monocytes can reflect the severity of CVD (Williams et al, 2021 ). In our study, the proportion of subjects who had hypertension, heart disease, and stroke in the SO group was higher than the proportion of similar subjects in the NSO group.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence demonstrated that metabolic disorders can trigger inflammatory responses as a coping mechanism toward metabolic changes, leading to chronic inflammation occur. Thereby, chronic inflammation is widely considered as common denominator in many diseases such as obesity, MetS, T2DM, and CVD ( 7 , 18 , 19 ). The inflammatory process is continuous when chronic inflammation occurs, WBCs play an important role and involved in the process of inflammation that can secrete inflammatory cytokines, which can initiate and upregulate inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating monocyte is a cluster of blood cell modulated by immune factors including tumor necrosis factors alpha (TNF-a) and Toll-like receptor (TLR) 2, TLR4, and TLR8 ligands that can interact with thrombocytes and endothelial cells, resulting in exaggerated inflammation and increased oxidative stress (4)(5)(6). These biological features provided a basis for monocyte involving in development of systematic inflammation disease like MetS, T2DM, and CVD (7). High-density lipoprotein (HDL-c) is considered as "good cholesterol" that can bind lipid molecules such as triglyceride (TG) and cholesterol and participate in the cholesterol clearance, resulting in decreased CVD risk (8).…”
Section: Introductionmentioning
confidence: 99%
“…увеличение доли и абсолютного количества промежуточных и неклассических моноцитов [10,32]. Промежуточные моноциты в сравнении с моноцитами других субпопуляций являются основными продуцентами IL-1β, IL-6 и TNFα, обладают наибольшей способностью к трансэндотелиальной миграции и образованию активных форм кислорода [8,34]. Наблюдаемое нами увеличение количества моноцитов, экспрессирующих CD36 и TLR2, по мере увеличения содержания HMGB1 также может свидетельствовать об активации преимущественно CD16 + моноцитов [15,28].…”
Section: Discussionunclassified